Metallization: New Metallic Ordered Phase of Perovskite CsPbI3 under Pressure (Adv. Sci. 14/2019). Issue 14 (17th July 2019) - Liang, Yongfu; Huang, Xiaoli; Huang, Yanping; Wang, Xin; Li, Fangfei; Wang, Youchun; Tian, Fubo; Liu, Bingbing; Shen, Ze Xiang; Cui, Tian
Abstract : In article number1900399, Xiaoli Huang, Fubo Tian, Tian Cui, and co‐workers track the bandgap evolution of perovskite CsPbI3 under pressure by a diamond anvil cell (DAC) device. The application of pressure reduces interatomic distances and profoundly modifies electronic orbitals and bonding patterns. Finally, a new metallic ordered phase of perovskite CsPbI3 is obtained at 39.3 GPa.